Potential of spiral breast computed tomography to increase patient comfort compared to DM. Issue 145 (December 2021) - Wetzl, Matthias; Wenkel, Evelyn; Dietzel, Matthias; Siegler, Lisa; Emons, Julius; Dethlefsen, Ebba; Heindl, Felix; Kuhl, Christiane; Uder, Michael; Ohlmeyer, Sabine
Highlights: Patients experience less pain during spiral breast computed tomography compared to DM. The effect of reduced pain compared to DM in spiral breast computed tomography is pronounced in premenopausal patients. Clinical workflow of SBCT is user-friendly. Spiral breast computed tomography could evolve as a clinically valuable imaging modality, especially in premenopausal patients or in cases of significant compression-related pain. Abstract: Purpose: To intra-individually compare patient comfort of spiral breast computed tomography (SBCT) versus digital mammography (DM). Method: This prospective IRB approved study included 79 patients undergoing both SBCT and DM for the assessment of BI-RADS 4 – 6 lesions. Following SBCT and DM patients answered a standardized questionnaire regarding "Overall patient comfort" and "Pain" on a 5-point Likert Scale. On the same Likert Scale, experienced radiologic technicians rated the workflow of the SBCT regarding patients' "Mobility", ease of patient "Positioning", patients' adherence to the examination ("Compliance") and expected image quality. Visibility of fibroglandular tissue in SBCT was independently rated by two breast radiologists on a 10-point Likert Scale. Subgroups stratified by menopausal status and body mass index (BMI) were analyzed. Results: Patients reported significantly lower pain during SBCT (4.73 ± 0.57) compared to DM (4.09 ± 0.90; P  < 0.01). This effect was independent from BMI. However, pain reduction by SBCT was most pronounced in premenopausal (SBCT vs. DM: 4.79 ± 0.50 vs. 3.89 ± 0.99) compared to postmenopausal patients (4.71 ± 0.77 vs. 4.20 ± 0.89). Overall patient comfort in premenopausal patients tended to be higher in SBCT compared to DM ( P = 0.08) . Radiologic technicians rated the SBCT procedure generally as positive (average: 4.62 ± 0.56). Coverage of fibroglandular tissue in SBCT was generally high (9.82 ± 0.43) and interrater agreement was good (κ = 0.77). Conclusions: Patients experience less pain during spiral breast computed tomography compared to DM, especially in premenopausal women. Imaging is feasible at a high level of anatomical breast coverage and without problems with the clinical workflow.